Application of the FMEA Method in Identifying Risks in the Process of Procurement - Putri, Erica Gratia; Ermawati, Wita Juwita; Priyarsono, Dominicus Savio (APMBA (Asia Pacific Management and Business Application), 2026)
The implementation of good corporate governance principles necessitates the integration of risk management across all operational activities, including procurement. At PT Riset Perkebunan Nusantara (PT RPN), several issues have been identified in the procurement process, including potential fraud, administrative inconsistencies, limited staff understanding of procurement procedures, and delays in supplier performance. These issues indicate that procurement risks stem not only from external factors but also from internal control deficiencies. This study applies Failure Mode and Effect Analysis (FMEA) to identify potential risk sources and evaluate their severity, likelihood of occurrence, and detectability. Data were collected through interviews with key stakeholders involved in the procurement process. The analysis generated Risk Priority Number (RPN) values ranging from 168 to 729, reflecting varying levels of vulnerability across different procurement stages. Each stage demonstrates a distinct risk profile in terms of impact, frequency, and the effectiveness of existing controls. The three highest-priority risks identified were C2 (RPN = 729), E1 (RPN = 648), and E3 (RPN = 630). These findings highlight the urgency of strengthening procurement governance to mitigate risks and enhance overall process reliability.